(untitled) (Scientific journal of the Fergana State University, 2024)
This article examines one of the new areas of linguistics – pragmalinguistics. Speech acts, which are one of the main areas of pragmalinguistics, and the tools that create them, are also taken into account. Information about the theoretical foundations and research methods is provided in detail. As a general theoretical method, the work uses methods of comparison, contrast, semantic and pragmatic analysis, and generalization. It was noted that intonation is one of the ways and means of creating speech acts. The types of speech acts are clearly indicated using linguistic data taken from fiction.